2023
DOI: 10.1161/hypertensionaha.122.20286
|View full text |Cite
|
Sign up to set email alerts
|

Independent Associations of Education, Intelligence, and Cognition With Hypertension and the Mediating Effects of Cardiometabolic Risk Factors: A Mendelian Randomization Study

Abstract: BACKGROUND: Education, intelligence, and cognition are associated with hypertension, but which one plays the most prominent role in the pathogenesis of hypertension and which modifiable risk factors mediate the causal effects remains unknown. METHODS: Using summary statistics of genome-wide association studies of predominantly European ancestry, we conducted 2-sample multivariable Mendelian randomization to estimate the independent effects of education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 65 publications
5
25
1
Order By: Relevance
“…In two‐step MR, we examined causal mediators according to the following criteria 14 : (1) there exists a causal association between education and the mediator and the effect of education on the mediator should be unidirectional to ensure the validity of the mediation model; (2) the causal association between the mediator and liver disease persists with adjustment for education; and (3) the association between education and the mediator and the association between the mediator and liver disease should be in opposite directions. In multivariable MR (MVMR) analyses, we selected genetic IVs of the combination of SNPs, which were genome‐wide significant in either the GWAS of education or the GWAS of mediator after clumping summary statistics from GWASs for LD threshold r 2 < 0.001 and distance>10 000 kb.…”
Section: Methodsmentioning
confidence: 99%
“…In two‐step MR, we examined causal mediators according to the following criteria 14 : (1) there exists a causal association between education and the mediator and the effect of education on the mediator should be unidirectional to ensure the validity of the mediation model; (2) the causal association between the mediator and liver disease persists with adjustment for education; and (3) the association between education and the mediator and the association between the mediator and liver disease should be in opposite directions. In multivariable MR (MVMR) analyses, we selected genetic IVs of the combination of SNPs, which were genome‐wide significant in either the GWAS of education or the GWAS of mediator after clumping summary statistics from GWASs for LD threshold r 2 < 0.001 and distance>10 000 kb.…”
Section: Methodsmentioning
confidence: 99%
“…18 Gaining deeper insights into the intricate relationship between education and health outcomes is instrumental in reducing disparities and enhancing overall population health. 14 A body of observational and MR studies have indicated that higher EA serves as a protective factor against oral diseases. behaviours and a spectrum of other capacities and opportunities that can be harnessed to enhance physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The random allocation of genetic variants during fertilization, mirroring the principles of randomised controlled trials, substantially diminishes the likelihood of confounding elements, such as sex and age, introducing bias into causal inferences. 14 Additionally, since genotype formation precedes the onset of diseases and is generally impervious to disease progression, the potential for reverse causality is considerably reduced. Recent MR investigations have robustly substantiated the causal relationship between EA and a diverse range of systemic disorders, encompassing hypertension, chronic liver diseases, oropharyngeal cancer and periodontitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations